2020
DOI: 10.1186/s12872-020-01623-w
|View full text |Cite
|
Sign up to set email alerts
|

New CHA2DS2-VASc-HSF score predicts the no-reflow phenomenon after primary percutaneous coronary intervention in patients with ST-segment elevation myocardial infarction

Abstract: Background: The no-reflow phenomenon (NRP) is a serious complication of primary percutaneous coronary intervention (PPCI) and is an independent predictor of poor prognosis. We aimed to find a simple but effective risk stratification method for the prediction of NRP. Methods: This retrospective single-center study included 454 consecutive patients diagnosed with acute STsegment elevation myocardial infarction (STEMI) and treated by PPCI, who were admitted to our emergency department between January 2017 and Mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Various studies have developed predictive models for the occurrence of NR in STEMI patients who underwent pPCI. These models were based on variables such as the atherogenic index of plasma (log TG/HDL-C) [ 15 ], the neutrophil-to-lymphocyte ratio [ 16 ], the lymphocyte-to-monocyte ratio [ 17 ], the fibrinogen-to-albumin ratio [ 18 ], R wave peak time [ 19 ], a combination of plasma D-Dimer and endothelin-1 levels [ 20 ], plasma D-Dimer and pre-infarction angina [ 21 ], a combination of pre-infarction angina and mean platelet volume to lymphocyte count ratio [ 22 ], the red cell distribution width–platelet ratio (RPR) [ 23 ], CHA2DS2-VASc [ 24 ] or CHA2DS2-VASc-HSF score [ 25 ], and some new risk scoring system [ 26 ]. Based on the AUC values, moderate accuracy was observed in this study, which is similar to previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have developed predictive models for the occurrence of NR in STEMI patients who underwent pPCI. These models were based on variables such as the atherogenic index of plasma (log TG/HDL-C) [ 15 ], the neutrophil-to-lymphocyte ratio [ 16 ], the lymphocyte-to-monocyte ratio [ 17 ], the fibrinogen-to-albumin ratio [ 18 ], R wave peak time [ 19 ], a combination of plasma D-Dimer and endothelin-1 levels [ 20 ], plasma D-Dimer and pre-infarction angina [ 21 ], a combination of pre-infarction angina and mean platelet volume to lymphocyte count ratio [ 22 ], the red cell distribution width–platelet ratio (RPR) [ 23 ], CHA2DS2-VASc [ 24 ] or CHA2DS2-VASc-HSF score [ 25 ], and some new risk scoring system [ 26 ]. Based on the AUC values, moderate accuracy was observed in this study, which is similar to previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…42–44 In another study, the new CHA 2 DS 2 -VASc-HSF score, which includes hyperlipidemia, smoking, and family history for coronary artery disease in addition to the classical score, was found to be an independent predictor of NR in patients with STEMI treated with pPCI. 17 The NR risk was increased in those with a score ≥2 in the study by İpek et al 45…”
Section: Discussionmentioning
confidence: 93%
“…615 Cheng et al 16 demonstrated higher levels of d -dimer and cystatin C in patients with NR in their study consisting of 218 acute anterior myocardial infarction (MI). In another study by Zhang et al, 17 HA 2 DS 2 -VASc-HSF score, defined as the new onset of congestive heart failure, hypertension, age (≥65 = 1 point, ≥75 = 2 points), diabetes, stroke/transient ischemic attack (2 points), and vascular disease (peripheral arterial disease, previous MI, and aortic atheroma), hyperlipidemia (H), smoking (S), and a family history of coronary heart disease (F), which includes hyperlipidemia, smoking, and family history for coronary artery disease in addition to classical score, was found to be an independent predictor of NR in patients with ST-elevation myocardial infarction (STEMI) treated with primary PCI (pPCI).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Andrianto et al 11 reported the better performance of CHA2DS2-VASc-HSF score in predicting of CAD severity compared with CHADS2 and CHADS2-VASc scores. In another study, 12 the CHA2DS2-VASc-HSF score was more successful in showing no-reflow phenomenon after PCI in patients with acute coronary syndrome compared with the CHADS2 and CHA2DS2-VASc scores. In addition, Kalyoncuoglu et al 13 found that the CHA2DS2-VASc-HSF score better predicted the 1-year cardiovascular outcomes and major adverse cardiac and cerebrovascular events compared with the CHADS2 and CHADS2-VASc scores in patients with NSTEMI.…”
mentioning
confidence: 94%